Quantifying the heterogeneity of cognitive functioning in Alzheimer's disease to extend the placebo-treatment dichotomy: Latent class analysis of individual-participant data from five pivotal randomized clinical trials of donepezil. Issue 1 (15th February 2021) - Levine, Stephen Z.; Goldberg, Yair; Yoshida, Kazufumi; Samara, Myrto; Cipriani, Andrea; Iwatsubo, Takeshi; Leucht, Stefan; Furawaka, Toshiaki A.
Abstract: Background: The extent and profiles of heterogeneity in cognitive functioning among participants in clinical trials of antidementia medication are unknown. We aimed to quantify and identify profiles of heterogeneity of cognition in Alzheimer's disease. Methods: Individual-level participant data were analyzed from five pivotal clinical trials of donepezil for Alzheimer's disease ( N = 2, 919). Based on Alzheimer's Disease Assessment Scale–Cognitive Subscale total scores from baseline up to week 12, a latent class model was used to identify heterogeneous groups. A logistic regression model was used to examine factors associated with group membership. Sensitivity analysis was conducted, restricted to the donepezil, and then the placebo arm. Results: The latent class model identified three classes labeled as low scorers (i.e., least cognitive impairment; N = 1, 666, 76.04%), improvers ( N = 27, 1.23%), and high scorers ( N = 498, 22.73%). Logistic modeling showed that donepezil compared to placebo was significantly ( p < 0.05) positively associated with membership in the improvers class (OR = 6.88, 95% CI = 2.03, 42.95), and negatively with high scorers (OR = 0.79, 95% CI = 0.64, 0.98). Sensitivity analysis restricted to the placebo, then donepezil arms replicated similar heterogeneity patterns. Conclusions: Our results inform clinicians regarding the extent of heterogeneity in cognitive functioning during treatment and contribute to trial design considerations.